1979
DOI: 10.1016/0092-8674(79)90246-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies of cloned sequences from four drosophila heat shock loci

Abstract: DNA cloned from the D. melanogaster (Oregon R) heat shock loci at 63BC and 95D codes for the 83,000 and the 68,000 dalton heat shock proteins, respectively. Both coding sequences occur once per haploid genome. Sequences complementary to messenger RNA for the 70,000 dalton heat shock protein are represented five times, twice at 87A and three times at 87 C. The copies at 87A differ characteristically from those at 87C in an interval of a few hundred bp near the 5' end of the messenger sequence, and the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0
6

Year Published

1981
1981
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(127 citation statements)
references
References 23 publications
3
118
0
6
Order By: Relevance
“…However, a short leader sequence could be missed by these methods. S1 mapping and DNA sequencing of a region preceding the 5 Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a short leader sequence could be missed by these methods. S1 mapping and DNA sequencing of a region preceding the 5 Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…One gene encodes the hsp 83 protein (4,5). This protein is abundant in uninduced cells and increases in heat shock induced cells (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Seventh, hsp83 mRNA is found in uninduced immature ovaries and early egg chambers, whereas other heat shock mRNAs are not detected (10). Finally, the hsp83 gene is the only heat shock gene known to contain an intervening sequence (2). Together, these observations indicate that expression of the hsp83 gene involves regulatory events at the levels of transcription, processing, and translation that are not shared by other heat shock genes.…”
Section: Introductionmentioning
confidence: 86%
“…Most genes active at 23°C are repressed while a specific set of heat shock genes is activated both at the transcriptional and translational levels (1). One of these induced genes, which encodes the 83,000 d heat shock polypeptide (hsp83), is a single copy gene located at the 63B cytogenetic locus of D. melanogaster (2). Several lines of evidence suggest that the expression of the hsp83 gene differs significantly from the other major heat shock genes of D. melanogaster.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have reported the presence of four introns in Hsp70 gene of the filamentous fungi N. crassa (Kapoor et al, 1995) and one intron in aquatic fungus Blastocladiella emersonii (Stefani and Gomes, 1995). Introns have been also found in Hsp83 of Drosophila (Holmgren et al, 1979) and Hsp70 of Caenorhabditis elegans (Snutch et al, 1988). The Hsp88 genomic DNAs from P. tenuipes Jocheon-1, P. tenuipes and C. militaris all contain 5 introns and 6 exons with the length of 13,62,32,1,438,306,288 bp, encoding 713 amino acid residues.…”
Section: Discussionmentioning
confidence: 99%